The Nystadt Peace and its Role in the Formation of Russian Statehood from 1721 to 1917 - O. V. Lebedeva (Vestnik MGIMO-Universiteta)
The article is devoted to studying the role and significance of the Nystadt Peace as a historical document reflecting the strengthening and importance of Russia in the world arena. The article studies the document's text using modern methods of political science research: content analysis, cognitive mapping, phonosemantic analysis. It shows that the Treaty of Nystad reflects the features of the formation of the internal political system of Russia, witnessed in the use of anthroponyms. It also reflects the features of the historical development of Russia: its gradual transformation into an empire, the absence of a banking system, merchants as an estate, a merchant fleet. The analysis of the document allows us to conclude that the agreement regulates interactions not only between Russia and Sweden but contains references to other European countries. It speaks of Russia's strengthening role in the international arena, not so much in the military but also in diplomatic terms. It is reflected in the ways the agreement is verbalized.The results of the phonosemantic analysis show a positive perception of the toponymy of geographic entities annexed to Russia under the terms of the Nystadt Peace. At the same time, the perception of Sweden and everything Swedish is characterized by negativism. Nystadt peace was vital for the development of Russia, its transformation into an empire, into an influential military force, for the modernization of the domestic governance system, the creation of new social institutions and practices, and the strengthening of domestic diplomacy.